Confirmation of the identity of the type host of the louse Halipeurus fallacis (Phthiraptera: Philopteridae) - Palma, Ricardo L. (Zootaxa, 2018)
Alexander (1954: 489) recorded a petrel (Aves: Procellariiformes) captured alive on board a ship in the Indian Ocean by Mr W.W.A. Phillips who, after removing some lice, liberated it the following morning. Alexander (1954) identified that petrel as the species “Pterodroma aterrima Bonaparte”, now placed in the genus Pseudobulweria. The lice were kept in the collection of the then British Museum (Natural History), now the Natural History Museum, London, England. Jouanin (1955) published a new species of petrel from the Indian Ocean as Bulweria fallax. Jouanin (1957: 19) discussed the identity of the petrel identified by Alexander (1954) as Pterodroma aterrima, stating that the descriptive data given by Alexander (1954) did not clearly fit either P. aterrima or B. fallax. However, considering the geographical coordinates where the bird was captured, Jouanin (1957) believed it was more likely Bulweria fallax.